2024
DOI: 10.1007/s12672-024-00866-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of DNA methylation of DNMT3A and TET2 with oral squamous cell carcinoma

Xueming Li,
Zaikun Li,
Qingxi Gao
et al.

Abstract: Oral squamous cell carcinoma (OSCC) is the sixth most common malignancy worldwide. Abnormal epigenetic modifications, including DNA methylation, are hallmarks of cancer and implicated in the development of various tumors. DNA methylation is catalyzed by the DNA methyltransferase and ten-eleven translocation dioxygenase families, with DNMT3A and TET2 being the most widely studied members, respectively. The correlation of methylation β values and clinical features was conducted in patients with OSCC in The Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, in sporadic colon adenocarcinomas, Cx43 expression is downregulated when TET-2 levels are low, which suggests that TET-2 functions to inhibit Cx43 and its potential to reduce tumors ( 44 ). In a different study, in vitro analyses revealed that TET2 overexpression and DNMT3A knockdown prevented oral squamous cell cancer from proliferating and migrating ( 47 ). The TET2/3 deletion also affects the microbiota, making the intestine more susceptible to inflammation during homeostasis and acute inflammation-induced mortality ( 48 ).…”
Section: Enzymes and Proteins Involved In Dnam And Ibdmentioning
confidence: 99%
“…However, in sporadic colon adenocarcinomas, Cx43 expression is downregulated when TET-2 levels are low, which suggests that TET-2 functions to inhibit Cx43 and its potential to reduce tumors ( 44 ). In a different study, in vitro analyses revealed that TET2 overexpression and DNMT3A knockdown prevented oral squamous cell cancer from proliferating and migrating ( 47 ). The TET2/3 deletion also affects the microbiota, making the intestine more susceptible to inflammation during homeostasis and acute inflammation-induced mortality ( 48 ).…”
Section: Enzymes and Proteins Involved In Dnam And Ibdmentioning
confidence: 99%